EFFECTIVENESS OF GROUP COUNSELING SERVICES TO HELP STUDENTS LEARNING DIFFICULTIES - Erlina Harahap (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The study is based on the problem of students still have difficulty in learning, the general problem of this research is "Are students able to overcome the difficulties of learning through group counseling services? Which is formulated as follows: Does the implementation of group counseling services can menagatasi learning difficulties students at SMAN 6 Padangsidimpuan. Objectives to be achieved is that the students know to overcome learning difficulties. The method used is True Experiment Design study with pretest-posttest form Experiment Group Design. With a sample experimental class is class XI IPA 1 as many as 10 students, and grade control as many as 10 students. Service group counseling conducted three meetings, the first meeting to implement pretest and implement all posstest treatment. From the results of operations to be carried, an increase ang big enough, especially the second meeting of the findings in the experimental group there were significant increases between posttest results. To test the hypothesis used by the formula Wilcoxon signed rank test using SPSS version 20 o'clock Wilcoxon test was used to analyze the results of observations from the two data are different or not. Average variable to overcome learning difficulties amounted to 150.00 (experimental group), while 131.60 (control group) have seen a very significant difference. It is advisable for teachers to provide insight to students in overcoming learning difficulties. For further research, is expected to make research on overcoming the difficulties of student learning through other methods